Identification of Key Blocks Considering Finiteness of Discontinuities in Tunnel Engineering - Yang, Yong; Wang, Shuhong; Zhang, Minsi; Wu, Bo (Frontiers in Earth Science, 2022)
Identification method of the block based on cutting algorithm has clear concept and is easy to implement, but it cannot limit the size of discontinuities. Based on the traditional cutting algorithm, an identification method of blocks based on meshing idea for tunnel engineering is proposed, which can realize the identification of blocks between finite-sized discontinuities and excavation surface. A visualization program for identifying and stability analysis of blocks is developed by using MFC and OpenGL, and then it is applied to the tunnel engineering. The shape and the number of the key blocks searched by this method are not limited, which is consistent with the actual engineering. In the case that the size of the discontinuities cannot be accurately obtained, the influence of the size change of the dominant discontinuity on the key block is discussed, which will make up the problem caused by the lack of parameters. The number and volume of key block are large when discontinuities are assumed to be infinite, and the calculation results are conservative. However, its volume and location have great reference value and guiding significance for practical engineering.